CRANIOTOPOGRAPHIC ANATOMICAL INDIVIDUAL VARIABILITY AND VARIANTS OF THE STRUCTURE OF THE DURA MATER SUPERIOR SAGITTAL SINUS OF THE SKULL VAULT IN PEOPLE OF MATURE AGE - Bondarenko, S.V.; Dubina, S.O.; Serbin, S.I.; Самойленко, О.В.; Rud, M.V.; Vilkhova, O.V. (World of Medicine and Biology, 2025)
For our investigation, we collected cadaveric material from 45 people of different ages and gender. We are proud of the sinus of investigations on macro-microscopic levels using advanced methods in morphology. The aim of our study was to establish the craniotopographical individual anatomical variability and variants of the structure of the superior sagittal sinus (SSS) of the dura mater of the brain of the cranial vault in adults. It has been revealed that the superior sagittal sinus has a close relationship with the bones of the skull vault, in connection with which it is possible to carry out a projection on these bones with the determination of craniometric points. It is quite possible to use these points in the fields of medical craniology and neurosurgery, taking into account the anatomical variability and variants of the structure of the superior sagittal sinus of the DMB of the cranial vault in adults during the implementation of surgical interventions during which intra- and extracranial venous-cerebral shunts will be created.